Bilateral Femoroacetabular Impingement: What is the Fate of the Asymptomatic Hip?. Issue 5 (May 2019) - Azboy, Ibrahim; Ceylan, Hasan Huseyin; Groff, Hannah; Vahedi, Hamed; Parvizi, Javad
Abstract: Background: Bilateral symptomatic femoroacetabular impingement (FAI) is common. However, the fate of asymptomatic hip in patients with the radiographic diagnosis of bilateral FAI and unilateral symptoms remains unknown. Questions/purposes: (1) What is the likelihood of the asymptomatic hip becoming painful in patients with unilateral symptoms but with radiographic evidence of bilateral femoroacetabular impingement? (2) What radiological and clinical factors are associated with the development of symptoms in an asymptomatic hip diagnosed with FAI? Methods: A longitudinally maintained institutional FAI database was queried to collect relevant data for this retrospective study. To answer our research questions, we created a cohort of patients with bilateral radiographic signs of FAI but only unilateral symptoms at the time of initial presentation. Between 2004 and 2016, a senior surgeon (JP) at one institution treated 652 patients for hip pain determined to be from FAI, a diagnosis we made based on clinical symptoms, physical exam, and diagnostic imaging. We excluded 95 patients (15%) because of inadequate data or other diagnoses, which left 557 patients. Of those, 170 patients (31%) had bilateral radiological diagnosis of FAI, and 88 (52%) of them had bilateral hip symptoms, and so were excluded. Of the remaining 82 patients, eight (10%) underwent bilateral FAI surgery under the same anesthetic despite having only unilateral symptoms, leaving 74 for analysis in this study. Patients were followed with annual clinic visits, or contacted by phone and electronically. We defined onset of symptoms using a modified Harris Hip Score (mHHS) or the University of California at Los Angeles (UCLA) activity scale, and used a logistic regression model to identify factors associated with the development of symptoms. Results: Of the 74 patients with bilateral FAI and an asymptomatic hip at initial presentation, 60 (81%) became symptomatic at a mean 2 years (range, 0.3–11 years) followup. Of these 60 patients, 43 (72%) eventually underwent subsequent surgical intervention. After controlling for potential confounding variables such as sex, age, BMI, history of trauma we identified that reduced neck-shaft angle (r = -0.243, p = 0.009), increased lateral center-edge angle (r = 0.123, p = 0.049), increased alpha angle (r = 0.069, p = 0.025), and younger age (r = -0.071, p = 0.046) were associated with the development of symptoms in the contralateral hip. With the numbers available, none of the other examined variables such as sex, BMI, history of trauma, psychiatric condition, employment, Tönnis grade, Tönnis angle, crossover sign, type of impingement, and joint congruency were found to be associated with symptom progression. Conclusions: Bilateral FAI may be observed about one-third of patients. Most patients with unilateral symptomatic FAI and radiographic diagnosis of bilateral FAI in this cohort became symptomatic relatively quickly and most of them underwent subsequent surgical intervention in the contralateral hip. Reduced neck-shaft angle, increased lateral center-edge angle, increased alpha angle, and younger age were associated with symptom development in the contralateral hip. Hip preservation surgeons may use the finding of this study to counsel patients who present with bilateral FAI but only unilateral symptoms about the natural history of their condition. Level of Evidence: Level III, therapeutic study.